Measles virus selectively blind to signaling lymphocyte activity molecule has oncolytic efficacy against nectin‐4‐expressing pancreatic cancer cells. Issue 11 (November 2016) - Awano, Mutsumi; Fujiyuki, Tomoko; Shoji, Koichiro; Amagai, Yosuke; Murakami, Yoshinori; Furukawa, Yoichi; Sato, Hiroki; Yoneda, Misako; Kai, Chieko
Abstract : Pancreatic cancer is one of the most intractable cancers and has a devastating prognosis; over the past three decades the 5‐year survival rate has been <10%. Therefore, development of a novel anticancer treatment for pancreatic cancer is a matter of urgency. We previously developed an oncolytic recombinant measles virus (MV), rMV‐SLAMblind, that had lost the ability to bind to its principal receptor, signaling lymphocyte activity molecule (SLAM), but which selectively infected and efficiently killed nectin‐4‐expressing breast and lung cancer cells. In this study, we analyzed the antitumor effect of this virus against pancreatic cancer. Nectin‐4 was expressed on the surface of 4/16 tested pancreatic cancer cell lines, which were efficiently infected and killed by rMV‐SLAMblind in vitro . The intratumoral inoculation of rMV‐SLAMblind suppressed the growth of KLM1 and Capan‐2 cells xenografted in SCID mice. The sequence analysis of MV isolated from the tumor revealed that the designed mutation in the H protein of rMV‐SLAMblind had been stably maintained for 47 days after the last inoculation. These results suggest that rMV‐SLAMblind is a promising candidate for the novel treatment of pancreatic cancer. Abstract : We demonstrate that pancreatic cancer cell lines express nectin‐4, a receptor molecule of measles virus, and that recombinant oncolytic measles virus (rMV‐SLAMblind) shows an effective antitumor activity against these pancreatic cancer cell lines. We also showed the stability of this virus genome in xenotransplanted tumors.